ANALISIS RETURN ON ASSET (ROA) DAN DEBT TO EQUITY (DER), TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI - Haniatus Sa’diyah, 13.05.62.0009; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2017)
This research is a research that analysize return on asset (roa) and debt to equity (der), against company value with corporate social responsibility (csr) as a moderating variable in companies listed in Indonesiaâs stock exchange of garment and textile sectors. Sampling method using purposive sampling with research period of 2012 until 2014. The sampel used consisted of 17 companies listed on the BEI. And the method of numerical analysis is formulated to the hypothesis. The results of the study showed that positive ROA, DER and CSR have no significant positive effect on firm value. While CSR is able to moderate the influence of ROA on company value.Keywords: Return On Asset, Leverage, Corporate Social Responsibility, and The Value of The Company